Sporočilnost poštnih znamk v obdobju družbenopolitične tranzicije na območju nekdanje Jugoslavije - Gosar, Anton (Geografski vestnik, 2022)
Images, text and currency on postage stamps represent and promote the country. The political or ideological orientation and the cultural dominance of the nation are on stamps visual and verbal imprints of a certain time. In this paper, we’ve analysed expressions (image and text) on 851 postage stamps that were issued in two periods, 1987–1991 in Yugoslavia and 1991–1995 in Slovenia and Croatia. In a step further we’ve studied just »occasional postage stamps« (535 stamps) that have been classified into five thematic groups. We foundout that in 315 cases the »occasional postage stamps« deal with political or national contents. Before the breakup of Yugoslavia, postage stamps glorified the resistance against the WW2 occupiers, socialism and the country’s successful international activities. The first images on postage stamps of Slovenia and Croatia depict important historical figures and events, mainly from the period of the national awakening in the 19th century.
Keywords: Croatia; Hrvaška; Jugoslavija; political geography; politična geografija; postage stamps; poštne znamke; Slovenia; Slovenija; Yugoslavia